Improving Mathematical Reasoning Skills Through a Discovery Learning Model for Junior High School Students in Karawang Dstrict - Apriyanti Apriyanti (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
The purpose of this study was to determine the improvement of mathematical reasoning ability through the discovery learning model for students in one of the junior high schools in Karawang Regency. This research used quantitative approach with quasi-experimental method and nonequivalent control group design. This research was conducted on junior high school students in grade VIII with purposive sampling technique. The sample of this study consisted of two classes, namely class VIII C received a direct learning model and class VIII E received a discovery learning model. Each class amounted to 35 out of 432 students in class VIII. The research results were processed using the Mann-Whitney test. Based on the data processing, it was found that there was an achievement and improvement in mathematical reasoning ability of students who obtained discovery learning model better than direct learning.